Relevant worlds : current perspectives on language, translation, and relevance theory - Wałaszewska, Ewa (Cambridge Scholars Pub., 2008)
The present volume examines Relevance Theory, one of the most influential pragmatic approaches to communication rooted in human cognition, by testing both its internal coherence and its applicability to such forms of communication as translation and literature. Part I addresses a wide range of issues which, over recent years, have been of central interest to pragmatists, including relevance theorists, but may well appeal to readers less familiar with pragmatic theory. The papers discuss selec ...